1968
DOI: 10.1037/h0025521
|View full text |Cite
|
Sign up to set email alerts
|

Concept attainment by individuals versus cooperative pairs as a function of memory, sex, and concept rule.

Abstract: The performance of individuals and cooperative pairs was compared on 3 successive concept-altainmenl problems. A2X2X2X8X3 repeated-measures factorial design was employed with the variables: number of persons (individual or cooperative pair), memory (paper and pencil for recording allowed or not allowed), sex (male or female), concept rule (concepts defined by 8 different symbolic logic operators), and problems (3 per S or Ss). Major results were: (a) for cooperative pairs fewer card choices to solution, more u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…In a study of recall in information processing, there was less improvement for women than for men as individuals (I) but more improvement for women than for men in groups (CG5; Morrissette et al, 1964r). In concept attainment (Laughlin, McGlynn et al, 1968r), male groups (CG2) made more use of focusing strategies than did either female groups (CG2) or male/female individuals (I), suggesting that men benefited more than women from working with a partner. Significant higher order interactions were found for Sex X Number of Persons X Problem Type and for Sex X Memory Aids X Number of Persons.…”
Section: Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of recall in information processing, there was less improvement for women than for men as individuals (I) but more improvement for women than for men in groups (CG5; Morrissette et al, 1964r). In concept attainment (Laughlin, McGlynn et al, 1968r), male groups (CG2) made more use of focusing strategies than did either female groups (CG2) or male/female individuals (I), suggesting that men benefited more than women from working with a partner. Significant higher order interactions were found for Sex X Number of Persons X Problem Type and for Sex X Memory Aids X Number of Persons.…”
Section: Individual Differencesmentioning
confidence: 99%
“…In one case (Terman Concept Mastery Test), however, a high-ability individual was superior to dyads and quads (e.g., H > MMMM and H > HLLL). In concept attainment, member ability was inconsistent across trials (Laughlin, McGlynn et al, 1968r). Only two studies (Laughlin et al, 1976r;Lemke et al, 1969r), however, reported tests of significant differences among high, medium, and low scorers.…”
Section: Individual Differencesmentioning
confidence: 99%
“…Earlier studies have produced equivocal findings concerning the improvement in all conditions over problems. Results indicated no improvement (Laughlin, 1966;Laughlin & Jordon, 1967;McGlynn, 1972; Anderson, Note 1), improvement for cooperative, vocalizing pairs but not for competing pairs or cooperative, nonvocalizing pairs (McGlynn & Schick, 1973a), or improvement regardless of conditions (Laughlin & McGlynn, 1967;Laughlin et al, 1968;McGlynn & Schick, 1973b;Schick & McGlynn, in press). Only two of these studies (McGlynn & Schick, 1973b;Schick & McGlynn, in press) used both the empirically superior memory manipulation of physically moving cards to spaces designated "example" or "non-example" and the reduced information feedback technique, which provides more behavioral data without affecting development of problem-solving processes and eliminates confounding that occurs when subjects guess the correct concept rather than solving the problem.…”
mentioning
confidence: 97%
“…Experimental evidence (e.g., Barnlund, 1959;Duncan, 1959;Gurnee, 1962;Hoffman, 1965;Lorge, Fox, Davitz, & Brenner, 1958) has indicated that groups may be superior to individuals on problem-solving tasks and concept attainment paradigms are problem-solving tasks particularly suited to programmatic study (Bruner, Goodnow, & Austin, 1956). In order to investigate the group-individual variable, a series of concept attainment studies contrasted silent individuals with groups who were given either a cooperative or competitive set and were either allowed or forbidden to converse (Laughlin, 1965;Laughlin & Doherty, 1967;Laughlin & Mc-Glynn, 1967;Laughlin, McGlynn, Anderson, & Jacobsen, 1968;McGlynn, 1972;McGlynn & Schick, 1973a). In all cases, individuals were inferior to groups, but the group results were less conclusive.…”
mentioning
confidence: 99%
“…Studies of cooperative cognition and multiperson problem solving are fairly rare in standard cognitive experimental settings where variables can be controlled in ways that are not practical in organizational or educational settings. Yet they are recommended (e.g., Meacham & Emont, 1989) and sometimes are done (e.g., Laughlin, 1965;Laughlin & Bitz, 1975;Laughlin, McGlynn, Anderson, & Jacobson, 1968;Rogers, Sinnott, & Van Dusen, 1991).…”
Section: Points Of Potential Interface: Cognition and Spiritualitymentioning
confidence: 98%